The influence of work life balance and work environment on employee performance through job satisfaction: a study at BNI Kebumen branch office - Dewi, Liana Etika; Helmy, Irfan (Institute of Computer Science (IOCS), 2025)
he performance of the BNI Kebumen Branch Office in 2023, as measured by a Performance Management System (PMS) score of 2.55 (equivalent to 51% achievement), indicates a level of performance below organizational expectations. This underscores the need for improvements across various internal and external factors. This study aims to examine the direct effects of work-life balance (WLB) and the work environment on employee performance, as well as their indirect effects mediated by job satisfaction. A quantitative research approach was employed, involving a total population of 50 employees using saturated sampling. Data were analyzed using inferential statistical methods through Structural Equation Modeling (SEM). The results reveal that WLB does not have a significant direct effect on employee performance. In contrast, both the work environment and job satisfaction show significant positive effects on performance. Additionally, WLB does not significantly influence job satisfaction, whereas the work environment has a positive and significant impact. Job satisfaction does not mediate the relationship between WLB and employee performance but does mediate the relationship between the work environment and employee performance. These findings highlight the pivotal role of a supportive work environment in enhancing both job satisfaction and overall employee performance